2016
DOI: 10.3390/ijms17091393
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of the Major Components of Diesel Exhaust in Human Alveolar Basal Epithelial Cells (A549)

Abstract: We investigated the toxicity of benzo[a]pyrene (B[a]P), 1-nitropyrene (1-NP) and 3-nitrobenzanthrone (3-NBA) in A549 cells. Cells were treated for 4 h and 24 h with: B[a]P (0.1 and 1 μM), 1-NP (1 and 10 μM) and 3-NBA (0.5 and 5 μM). Bulky DNA adducts, lipid peroxidation, DNA and protein oxidation and mRNA expression of CYP1A1, CYP1B1, NQO1, POR, AKR1C2 and COX2 were analyzed. Bulky DNA adducts were induced after both treatment periods; the effect of 1-NP was weak. 3-NBA induced high levels of bulky DNA adducts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 37 publications
(62 reference statements)
2
21
1
Order By: Relevance
“…Levels of BaP‐DNA adducts in TT1 cells were 66‐fold lower than 3‐NBA‐DNA adducts. It is noteworthy that the observed BaP‐DNA adduct levels in TT1 cells are low compared to other published studies [Hockley et al, ; Rossner et al, ; Shi et al, ]. In this study, we showed induction of CYP1A1 in TT1 cells and not a genotoxic response, and hence, this might be reflective of increased repair of BaP‐DNA adducts in the TT1 cell line in the timeframe studied, or a stronger detoxifying effect of CYP1A1; further work is warranted to understand this.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…Levels of BaP‐DNA adducts in TT1 cells were 66‐fold lower than 3‐NBA‐DNA adducts. It is noteworthy that the observed BaP‐DNA adduct levels in TT1 cells are low compared to other published studies [Hockley et al, ; Rossner et al, ; Shi et al, ]. In this study, we showed induction of CYP1A1 in TT1 cells and not a genotoxic response, and hence, this might be reflective of increased repair of BaP‐DNA adducts in the TT1 cell line in the timeframe studied, or a stronger detoxifying effect of CYP1A1; further work is warranted to understand this.…”
Section: Discussioncontrasting
confidence: 42%
“…Finally, the concentrations used in the study are higher than humans would be exposed to under realistic exposure scenarios. For example, Rossner et al [] suggested that for an ambient concentration of BaP of 0.1–10 ng/m 3 in air this would represent femtomolar concentrations of BaP in culture medium. On the other hand, human lungs are typically chronically exposed to low levels of air pollutants, which is difficult to mimic in any cell culture models.…”
Section: Discussionmentioning
confidence: 99%
“…In general, most of the parent compounds are detoxified. However, PAH metabolism can be harmful to cells, through the production of highly reactive electrophilic metabolites as well as reactive oxygen species (ROS) which then damage cellular macromolecules such as DNA, lipids or proteins [39][40][41][42][43]. The diol-epoxide metabolites are considered to be the most mutagenic and tumorigenic, notably through the formation of DNA-adducts [44][45][46].…”
Section: Formation and Binding Of Reactive Metabolitesmentioning
confidence: 99%
“…The diol-epoxide metabolites are considered to be the most mutagenic and tumorigenic, notably through the formation of DNA-adducts [44][45][46]. In addition, the related ROS production may also lead to DNA damage [47,48], through the formation of 8-oxo-7,8-dihydro-2'-deoxyguanosine (8-oxodG) [39,41,43]. Both types of DNA damages, if not repaired, may then lead to important consequences in terms of DNA mutations [43][44][45][46], or to activation of cell death processes [49].…”
Section: Formation and Binding Of Reactive Metabolitesmentioning
confidence: 99%
“…However, AhR is a mediator of the toxicity for several xenobiotics: the PAH prototype benzo[a]pyrene (Ba[P]) is rapidly metabolized by cytochromes P450 and aldo-keto reductases and produces diol-epoxide metabolites that are mutagenic and tumorigenic, notably through the formation of DNA-adducts [10]. Moreover, AhR-dependent detoxification leads to oxidative stress and reactive oxygen species (ROS) production resulting in oxidative damage on cellular macro-molecules such as DNA, lipids or proteins [11][12][13].…”
Section: -1 Canonical Role Of Ahr : Xenobiotic Metabolismmentioning
confidence: 99%